Synthesis of 1-Substituted-2-thio-1H-4-[(2-imino-4-thiobiureto-5-yl) guanyl]-6-substituted amino-1,2-dihydro-s-triazines - SHELKE, M.E.; TAYADE, D.T. (Asian Journal of Chemistry, 2010)
Series of 1-substituted-2-thio-1H-4-[(2-imino-4-thiobiureto-5-yl)-guanyl]-6-substitutedamino-1,2-dihydro-s-triazines [(4a(i)-4f(iv)] have been obtained by the isomerization of 2-substituted amino-4-(2-imino-4-thiobiureto-5-yl-carbamidino)-6-substitutedimino-1,3,5-thiadiazines [3a(i)-3f(iv)] in presence ·of ethanolic sodium bicarbonate solution, which have been obtained by basification of their hydrochlorides [2a(i)-2f(iv)] which are synthesized by the interaction of 1-formamidino-3-thioamido-N-substituted formamidinothiocarbamides (1a-f) and N-aryl/alkylisocyanodichlorides. The latter were prepared initially by the condensation of N-aryl/alkylisothiocyanate and 1,3-diformamidinothiocarbamide. The structure of all these compounds was established on the basis of elemental analysis and IR and NMR spectral data.